SQUARING A CIRCLE? Sustainability Reports as a Legitimacy-Seeking Strategy in State Gambling Monopolies - Caruana, Albert; Vella, Joseph; Konietzny, Jirka (Critical Gambling Studies, 2025)
State gambling organisations are monopolies, that increasingly proclaim a commitment to sustainability principles, however their profits come at a substantial social cost. Gambling raises an array of economic, social and ethical governance concerns. This study examines the evolution of sustainability, corporate social responsibility (CSR), environmental, social and governance (ESG) practices, and the growing trend of publishing annual sustainability reports. These aspects are considered within the literature on organisational legitimacy, and a framework of legitimacy-seeking strategies is identified. Qualitative research is utilised to analyse sustainability reports published during 2021-2022 by two state gambling monopolies: the British Columbia Lottery Corporation (BCLC) in Canada and Veikkaus in Finland. Using Leximancer software, content analysis identified key themes that can be linked to legitimacy strategies and gambling-related concerns. Findings suggest that while sustainability reports enhance organisational legitimacy, fundamental ethical and social challenges persist, requiring more deliberate managerial approaches.